(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
It is known that new directions and fields are being studied in linguistics today. This article also provides general information about media text. At the same time, mediatext- linguistics is the interest of many disciplines, which is mainly explained by the essence of mass communication, and the study of mediatexts in linguistics provides information about their types. In addition, the functional grouping of media texts and their characteristics are explained. It can be added that the divisions in media texts are different by linguists and their differences are explained.